Respuestas

2013-04-10T08:02:35+02:00

Ecuación 1.

 

6/x + 5/y = 8     ==>     6/x = 8 - 5/y     ==>     1/x = 8/6 - 5/6y     ==>     1/x = 4/3 -5/6y      Ecuación 3

 

Ecuación 2.

 

7/x + 2/y =17    ==>   7/x = 17 - 2/y   ==>     1/x = 17/7 - 2/7y     Ecuación 4.

 

Igualando las ecuaciones 3 y 4

 

4/3 -5/6y = 17/7 - 2/7y    ==>    2/7y - 5/6y = 17/7 - 4/3    ==>    (12-35)/42y = 23/21

 

==>   -23/42y = 23/21    ==>   -23/23 = 42y/21     ==>    2y = -1   ==>   y = -1/2

 

Remplazando "y" en la ecuación 3

 

1/x = 4/3 -5/[6(-1/2)]   ==>   1/x = 4/3 + 5/3     ==>    1/x = 9/3     ==>   1/x =3    ==>   x = 1/3

 

Resp.       x = 1/3    y = -1/2